Hubungan Kekerabatan Fenetik Pisang di Kecamatan Kabawetan, Kabupaten Kepahiang, Provinsi Bengkulu - Riandini, Evelyne (Al-Hayat: Journal of Biology and Applied Biology, 2020)
Study of the genetic relationship between bananas carried out in Kabawetan Subdistrict, Kepahiang District, Bengkulu Province, from April to October 2019. Data collection on banana exploration studies is carried out in several locations of houses and community gardens in the form of wild plants and cultivation. Morphological data were compiled based on observations of morphological characters of specimens in the field, the character status was adapted from banana descriptors (IPGRI 1996). Morphological characterization results were observed and continued with character selection based on kinship in the form of a tree phenogram. Data were analyzed using the Numerical Taxonomy System (NTsys-pc) 2.02 program with the Unweight Pair Group Arithmetic Mean Method (UPGMA). The results found 6 types of banana diversity collection from 32 pseudo stands (individuals). The collection results obtained in the field are 1 collection of wild bananas and 5 cultivation collections. There are 6 banana distribution locations, namely Mekasari Village, Sumbersari Village, Babakan Village Bogor, Sumbersari Village, Tugu Rejo Village, Sido Rejo Village. Kinship of 6 types was found to have a similarity coefficient between 0.27 - 0.63. Phenograms divide into 2 large groups of 6 types of bananas, namely group A and group B, these two groups are separated by a similarity coefficient value of 0.27. Group A has a total of 5 types of bananas namely kapal, kapok , gembor, and jantan bananas.